2022
DOI: 10.1002/alz.062391
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of myeloid cells in Alzheimer’s Disease brain illustrates heterogeneity of microglia endolysosomal subtypes

Abstract: BackgroundMicroglia‐mediated neuroinflammation contributes to disease progression in Alzheimer’s Disease (AD). Microglia demonstrate heterogeneous states with proposed beneficial, harmful, and disease‐specific subtypes. Defining the spectrum of microglia phenotypes is crucially important to the design of neuroinflammation‐modulating therapies.MethodWe performed single‐nucleus RNA‐seq on over 120,000 microglia nuclei isolated from dorsolateral prefrontal cortices collected from 12 AD and 10 controls. Nuclei wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the ability to study microglia subtypes in living patients remains challenging using existing PET targets. This represents a current limitation of in vivo brain imaging, especially considering molecular studies have identified several microglia subtypes with unique functional roles in AD ( Kamphuis et al, 2016 ; Krasemann et al, 2017 ; Frigerio et al, 2019 ; Olah et al, 2020 ; Prater et al, 2021 ). This includes disease-associated microglia (DAM), which have enhanced phagocytic and lipid metabolism pathways ( Keren-Shaul et al, 2017 ).…”
Section: In Vivo Imaging Of Brain and Retinal Microglia In N...mentioning
confidence: 99%
“…However, the ability to study microglia subtypes in living patients remains challenging using existing PET targets. This represents a current limitation of in vivo brain imaging, especially considering molecular studies have identified several microglia subtypes with unique functional roles in AD ( Kamphuis et al, 2016 ; Krasemann et al, 2017 ; Frigerio et al, 2019 ; Olah et al, 2020 ; Prater et al, 2021 ). This includes disease-associated microglia (DAM), which have enhanced phagocytic and lipid metabolism pathways ( Keren-Shaul et al, 2017 ).…”
Section: In Vivo Imaging Of Brain and Retinal Microglia In N...mentioning
confidence: 99%